An automated methodology for mode II delamination tests under fatigue loading based on the real time monitoring of the specimen's compliance. (January 2016) - Renart, J.; Vicens, J.; Budhe, S.; Rodríguez-Bellido, A.; Comas, J.; Mayugo, J.A.; Costa, J.
Highlights: A robust and automated method to perform fracture fatigue tests is proposed. The procedure relies on the continuous monitoring of the dynamic compliance. Onset of fatigue propagation is determined with the precision of one cycle. Continuous crack growth rate curves are obtained. Transient effects of temperature and friction were analysed in a mode II ENF test. Abstract: This work introduces a procedure based on the real time monitoring of the specimen's compliance for the experimental characterization of the fatigue behaviour of interlaminar cracks in composites. The methodology was applied to a mode II loading in a three-point end notch flexure test. The onset point for fatigue damage was determined with a precision of one cycle by establishing a threshold on the compliance variation from its initial value. On the other hand, the crack growth rate curve was derived from the continuous monitoring of the compliance and an experimental calibration of said compliance. The precision of this methodology allowed the effect of commonly neglected phenomena such as the thermal expansion of the testing system or the friction between the specimen and the fixture, to be unveiled.